PENGUATAN KARAKTER NASIONALISME PESERTA DIDIK MELALUI HABITUASI DI WILAYAH PERBATASAN INDONESIA DAN MALAYSIA (STUDI DI SMP NEGERI 1 SEBATIK TENGAH) - Andi Aco Agus; Imam Suyitno; Era Fasirah (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2024)
This research aims to find out: (1) The strategies used by schools to strengthen the nationalist character of students through habituation at SMP Negeri 1 Sebatik Tengah. (2) Supporting and inhibiting factors in the implementation of strengthening the nationalist character of students at SMP Negeri 1 Sebatik Tengah. This research is qualitative research with a qualitative descriptive approach, the types of data used in the research are primary data and secondary data. Data collection techniques were obtained through observation, interviews and documentation. The results of the research show that: (1) The strategy used by schools to strengthen the nationalistic character of students is through habituation in the form of flag ceremony activities, singing the national anthem before and after learning, use of Indonesian then scout extracurricular activities, teacher example, and Learning based on local wisdom, namely Yameto and Lukiwol regional gymnastics. This habituation program has very important benefits and contributions in supporting the strengthening of students' nationalistic character. (2) Supporting and inhibiting factors in the implementation of strengthening the nationalist character of students at SMP Negeri 1 Sebatik Tengah (a) Supporting factors are the active role of teachers, consistency and regularity in carrying out habituation activities. (b) inhibiting factors, namely the influence of the living environment.